Research on kinematics of 3-dof connecting rod manipulator based on 5R kinematic chain: Take the bionic pelican fishing device as an example (International Journal of Scientific Research and Management (IJSRM), 2023)
Based on the flexibility of the neck manipulator of the bionic pelican fishing device, the demand for carrying capacity and the consideration of economic benefits, a 3-DOF connecting rod manipulator based on the 5R kinematic chain was designed, and the kinematic characteristics of the 5R five-bar mechanism in two-dimensional space and the mobility of the mechanism under the constraint of the bar length were studied. Through the application of matlab simulation, the movable range of the mechanism is obtained and the data analysis of the predetermined track is realized within the movable range, and the angle change curve chart required for the motor to achieve the predetermined track is obtained. The predetermined movement track is simulated by using the corresponding data and motion characteristics of the curve chart, which verifies the feasibility of achieving the target tracksetting within the movable range of the track.